Cysteinyl leukotriene receptor 1 as a host determinant for susceptibility to cutaneous leishmaniasis in a mouse model - Cele, Zama (Department of Molecular and Cell Biology, 2024)
Leishmaniasis is a vector-borne neglected tropical disease caused by Leishmania parasites. Approximately one million Leishmania infections are reported annually with one billion people residing in 98 countries at risk of infection. Cutaneous leishmaniasis (CL), characterized by skin lesions caused by Leishmania major and other species including Leishmania tropica and Leishmania aethiopica,is the most common form of the disease. With no effective vaccine, drug treatment is fraught with complications hence leishmaniasis is a major global public health burden. Interestingly, not all infected people develop active disease showing that an in-depth understanding of immune mechanisms could allow clear criteria for developing alternate host- derived therapies. Leukotrienes (LTs), produced by macrophages and other phagocytic cells including neutrophils, mast cells and dendritic cells during arachidonic acid metabolism, are hypothesized to induce a protective response during cutaneous leishmaniasis. However, as LTs consist of cysteinyl leukotrienes (CysLTs- LTC4, LTD4, LTE4) and LTB4, it is unclear which LT subclass is responsible for this protection. Recent studies suggested treatment of cutaneous leishmaniasis infected animals with cysteinyl leukotrienes induce host protection. To investigate this further, we targeted CysLTs via one of its receptors, cysteinyl leukotriene receptor 1 (CysLTR1), for its role in resistance or susceptibility to L. major-induced CL. In male and female BALB/c mice homozygous deficient for CysLTR1, we found that disease progression, parasite burdens, antibody and cytokine responses showed no significant alteration when compared to control animals with normal CysLTR1 expression. Importantly, expression of CysLTR2 did not appear to compensate for lack of CysLTR1 in CysLTR1-/- mice. Overall, these findings indicate that CysLTR1, as a host factor, is dispensable to the non- healing response associated with CL caused by L. major in mice.